USING OF PROGRAM MODULE “CALCULATOR” FOF SOLVING OF SCHOOL PHYSICAL TASCS - Odintsov, B.B.; Vinnik, T.O. (Journal of Information Technologies in Education (ITE), 2010)
Methodical and technological questions connected with functionality of special educational software “Calculator” intended for solving of school physical tasks are considered. The first version of software is designed in Research institute of Kherson state university.